Managing Human Resources - Balkin David B.; Cardy Robert L; Gomez - Mejia Luis R (Prentice Hall International, 1995)
This book provides an engaging and effective approach to addressing human resource issues for students of all major, from marketing to finance and from management to accounting and economics. Introduction, Meeting Present and Emerging Human Resource Challenges, The Contexts of Human Resource Management, Planning and Implementing Strategic HR Policies, Managing the Structure and Flow of Work, Understanding Equal Opportunity and the Legal Environment, Managing Work Force Diversity, Staffing, Recruiting and Selecting and Socializing Employees, Managing Employee Separations and Outplacement, Employee Development, Appraising and Managing Performance, Training Employees, Developing Careers, Compensation, Managing Compensation, Rewarding Performance, Designing and Administering Benefits, Governance, Developing Employee Relations and Communications, Respecting Employee Rights and Managing Discipline, Working with Organized Labor, Managing Workplace Safety and Health, Contemporary Challenges, Meeting the International HRM Challenge, Managing Quality with Human Resources, Evaluating the Human Resources System.